Application of Bacteriophages to Control Vibrio alginolyticus Contamination in Oyster (Saccostrea glomerata) Larvae - Tuan Son Le; Paul C. Southgate; Wayne O'Connor; Sang V. Vu; D. İpek Kurtböke (MDPI AG, 2020)
Mortalities of bivalve larvae and spat linked with Vibrio spp. infection have been described in hatcheries since 1959, causing potential development of resistant bacteria. A reliable and sustainable solution to this problem is yet to be developed. Potential treatment of bacterial infection with bacteriophages is gaining interest in aquaculture as a more sustainable option for managing Vibrio spp. infection. This study assessed the effectiveness of bacteriophages (Φ-5, Φ-6, and Φ-7) against pathogenic Vibrio isolates (USC-26004 and USC-26005). These phage isolates were found to belong to the Myoviridae viral family. A total of 212 ORFs of Φ-5 were identified and annotated. The genome of this phage contained putative thymidine kinase and lysin enzyme. During infections with phages, the OD values of the isolates USC-26005 and USC-26004 remained stable at a much lower reading compared to the control after 9 h of incubation. Mortality rate of oyster (Saccostrea glomerata) larvae was 28.2 ± 3.5% in the bacteriophage treatment group, compared to 77.9 ± 9.1% in the bacterial treatment group after 24 h incubation. Findings of this study indicate that lytic phages might be utilized as potential bio-control agents of luminescent bacterial disease in oyster hatcheries.